Bond strength of resin composite to enamel submitted to at-home desensitizer and bleaching agents - Matheus Kury; Bruna Guerra Silva; Francine de Almeida Zandonadi; Leonardo Gonçalves da Cunha; Vanessa Cavalli (Brazilian Journal of Oral Sciences, 2021)
Aim: This study evaluated the effect of a desensitizer agent (DES) during bleaching with 10% carbamide peroxide (CP) on enamel microshear bond strength (μSBS). Methods: Sixty bovine incisors were obtained and randomly distributed into groups (n=15): (C) Control: no desensitizing or bleaching, (DES) desensitizing gel application, (CP) bleaching with 10% CP and (CP/DES) bleaching with 10% CP combined with DES. Bleaching was performed for 6 h/day for 14 consecutive days. DES was applied for 8 h only on the 7th and 14th days of therapy. Specimens were stored in artificial saliva among the CP or DES applications and submitted to μSBS testing at three postrestoration times (n=5): 24 h, 7 days, and 14 days after bleaching using a universal testing machine. Failure modes were observed under a stereomicroscope. Data were analyzed by two-way ANOVA and Tukey’s test (α=5%). Results: Immediately after bleaching (24 h), CP promoted lower μSBS than the C and DES groups (p<0.05) but with no differences from the CP/DES. μSBS increased in the DES, CP, and CP/DES groups (p<0.05) when bonding was performed for 7 or 14 days elapsed from bleaching. CP/DES exhibited the highest μSBS among the groups 14 days after bleaching (p<0.05). Cohesive failure in enamel was predominant in the CP groups, while adhesive failure was mostly observed for the other groups. Conclusion: The use of a desensitizer during at-home bleaching maintained the enamel immediate bond strength, and its application favored bonding when the restoration was delayed for 14 days.